Posttraumatic Stress in Patients With Inflammatory Bowel Disease: Prevalence and Relationships to Patient-Reported Outcomes. Issue 5 (17th June 2021) - Taft, Tiffany H; Quinton, Sarah; Jedel, Sharon; Simons, Madison; Mutlu, Ece A; Hanauer, Stephen B
Abstract: Background: Patients with chronic illness are at increased risk for traumatic stress because of medical trauma. Initial studies of posttraumatic stress (PTS) in patients with inflammatory bowel disease (IBD) have found that approximately one-third of patients may experience significant PTS symptoms including flashbacks, nightmares, hypervigilance, disrupted sleep, and low mood. We aim to better characterize PTS in IBD and its relationship with patient outcomes in a large cohort of patients with IBD. Methods: Adult patients registered with the Crohn's & Colitis Foundation/University of North Carolina IBD Partners database were invited to complete a supplementary survey between February and July 2020. The Post Traumatic Stress Disorder Checklist-5th edition was administered as a supplemental survey. Additional data from IBD Partners included disease severity, surgery and hospital history, demographics, and health care utilization. Results: A total of 797 patients participated (452 with Crohn disease, 345 with ulcerative colitis). No impacts on response patterns because of the COVID-19 pandemic were found. Although 5.6% of the sample reported an existing PTS diagnosis because of IBD experiences, 9.6% of participants met the full IBD-related PTS diagnostic criteria per the Post Traumatic Stress Disorder Checklist-5th edition. Female patients, younger patients, those with less educational attainment, non-White patients, and Hispanic patients reported higher levels of PTS symptoms. Patients with higher PTS symptoms were more likely to have been hospitalized, have had surgery, have more severe symptoms, and not be in remission. Increased PTS was also associated with increased anxiety, depression, pain interference, fatigue, and health care utilization. Conclusions: The present findings support prior research that approximately one-quarter to one-third of patients with IBD report significant symptoms of PTS directly from their disease experiences, and certain demographic groups are at higher risk. In addition, PTS is associated with several IBD outcomes. Patients with higher PTS symptoms are less likely to be in remission and may utilize more outpatient gastrointestinal services. Intervention trials to mitigate PTS symptoms in patients with IBD are warranted.